2020
DOI: 10.1111/jopy.12562
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of the interplay between personality vulnerability and need‐based experiences in adolescents' depressive symptoms

Abstract: Adolescence is marked by an increased susceptibility to depressive symptoms, which has important repercussions for adolescents' personal, social, and educational development (Costello, Copeland, & Angold, 2011). Given that vulnerability to psychological difficulties is still susceptible to change in adolescence (Hauser, Allen, & Golden, 2006), it is important to gain more insight into factors that increase the risk for depressive symptoms in this developmental period. Such insight is needed to improve preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
4
13
1
Order By: Relevance
“…Consistent with the dual process model (Vansteenkiste & Ryan, 2013 ), need satisfaction was found to contribute primarily to individuals’ psychological well-being, as indexed by life satisfaction (Tay & Diener, 2011 ), vitality (Ryan & Deci, 2008 ), and meaning (Martela et al, 2018 ) as well as to their physical health, as indexed by increased longevity (Weinstein et al, 2019 ). In contrast, need frustration relates primarily to ill-being as indexed by symptoms of anxiety, stress, and depression (e.g., Bartholomew et al, 2011 ; Vandenkerckhove et al, 2020 ), while also predicting poor physical health, as indexed by poorer sleep quality (Campbell et al, 2017b ) and greater stress reactivity (Reeve & Tseng, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the dual process model (Vansteenkiste & Ryan, 2013 ), need satisfaction was found to contribute primarily to individuals’ psychological well-being, as indexed by life satisfaction (Tay & Diener, 2011 ), vitality (Ryan & Deci, 2008 ), and meaning (Martela et al, 2018 ) as well as to their physical health, as indexed by increased longevity (Weinstein et al, 2019 ). In contrast, need frustration relates primarily to ill-being as indexed by symptoms of anxiety, stress, and depression (e.g., Bartholomew et al, 2011 ; Vandenkerckhove et al, 2020 ), while also predicting poor physical health, as indexed by poorer sleep quality (Campbell et al, 2017b ) and greater stress reactivity (Reeve & Tseng, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not report findings on relatedness frustration in particular and did not assess need satisfaction or externalizing problems. Overcoming these limitations, Vandenkerckhove et al (2019) found relatedness frustration to be associated with internalizing problems but not externalizing problems, while they did not find relatedness satisfaction to be linked to either. In this study, relatedness satisfaction is associated with fewer internalizing problems (i.e., emotional symptoms and peer problems) and relatedness frustration is linked to more externalizing problems (i.e.,…”
Section: Summary Of Findings and Practical Implicationsmentioning
confidence: 75%
“…However, empirical evidence is still inconclusive on whether they differentially predict positive and negative outcomes in children and young adolescents. Studies have found relatedness satisfaction to be particularly predictive of adaptive outcomes such as positive affect (Schmidt et al, 2019), self-esteem (Schmidt et al, 2020b), and school satisfaction (Tian et al, 2018), whereas relatedness frustration was primarily associated with adverse outcomes such as negative affect (Schmidt et al, 2020a), maladjustment (Rodríguez-Meirinhos et al, 2020), or internalizing problems (Vandenkerckhove et al, 2019). However, other studies demonstrate global rather than differential effects: Earl et al (2019) found relatedness satisfaction to positively predict positive affect as well as vitality and to be negatively related to negative affect, while Bartholomew et al (2011) found relatedness satisfaction and frustration to both significantly predict vitality and exhaustion in the expected directions.…”
Section: Social Relatedness To New Classmatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Confronted with need frustration, adolescents whose personality vulnerability is heightened in the day would thus be less resilient against and more susceptible to the risks associated with need frustration and low need satisfaction. Although this possibility of moderation is theoretically plausible, the few studies to date that examined this possibility did not find support for it (Vandenkerckhove et al, 2020; Vandenkerckhove, Soenens, et al, 2019). None of these studies, however, examined the interactive interplay between Blatt's personality dimensions and need‐based experiences on a daily basis (instead focusing on stable interindividual differences or long‐term change).…”
Section: Introductionmentioning
confidence: 99%